Application and impact of 5G networks in industrial environments - Ladeira de Sousa, Alexandre; Lopes Rosa, Renata (INFOCOMP Journal of Computer Science, 2023)
5G figures today as one of the newest technologies that promises to further accelerate the information flow on the network. Its application is not limited to mobile telephony, but has also been adding value in the most diverse segments such as industry, medicine, agribusiness, logistics and even in war environments. Its most diverse possibilities also bring with it some prerequisites for installation, as well as development needs in the area of information security to guarantee the sustainability of its operation. Applied to industrial environments, 5G is able to bring benefits in the safety of people and equipment, optimization of workflows, prediction of failures in production chains, among other possibilities. This article sets out to understand, through a systematic mapping of the literature, the facts that preceded its creation, the minimum requirements for its operation, as well as the impacts and demands on the industrial environment with its application in production chains in general.